Effect of calcium carbide on the rate of ripening of Ambon Bananas (Musa paradisiaca Var. Sapientum (L). Kunt) - Loupatty, Jeyssen Lincon; Tuhumena, Gloria Eka Sari; Limba, Gysella Velove; Wariunsore, Ayu; Noya Van Delzen, Zipora V; Warella, Juen Carla; Rumahlatu, Gerce Anne (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2023)
Bananas are one of the most widely consumed sources of nutrients in Indonesia. Generally, bananas are consumed fresh and processed into various snacks. This leads to an increased demand for bananas in the market. However, the natural ripening process takes 7-8 days after harvest, which is a long time to meet consumer demand. One solution is to use calcium carbide to accelerate fruit ripening. The reason for using calcium carbide is that it is readily available and inexpensive, so banana producers use carbide as a fruit ripening agent. The objective of this study was to determine the effects of calcium carbide on fruit ripening of Ambon bananas. The method used was a laboratory experiment with a post-test-only control group design. There were three treatments with calcium carbide concentrations of 12%, 6%, and 3%, and positive control, namely rapining with rice. Data were analyzed descriptive qualitative by collecting, presenting, reducing, and conclusions. The process of fruit ripening can be observed using the variables of color, texture and aroma. The results obtained were differences in color, texture, and aroma at concentrations of 12%, 6%, and 3% based on the length of aging. Based on the color parameter, the concentration of 6% and 12% showed a blackish yellow/brown color, while the concentration of 3% was yellow with black spots. The texture parameters of the 6% and 12% concentrations had a very soft texture, while the 3% concentration had a smooth texture. The aroma parameters of the 12%, 6%, and 3% concentrations had a rancid aroma on day six, while days one, two, and three were fragrant. The conclusion is that using calcium carbide at different concentrations affects the rate of fruit ripening. The higher the concentration of calcium carbide used, the faster the respiration rate of the bananas, thus initiating the ripening process